Quaternized Pyridyloxy Phthalocyanines Render Aqueous Electron-Donor Carbon Nanotubes as Unprecedented Supramolecular Materials for Energy Conversion - Anaya-Plaza, Eduardo; Moreno-Oliva, Maria; Kunzmann, Andreas; Romero-Nieto, Carlos; Costa, Ruben Dario; De La Escosura, Andres; Guldi, Dirk Michael; Torres, Tomas (Advanced Functional Materials, 2015)
Exploring new properties in known materials, sometimes even achieving behaviors opposite to those traditionally encountered, is a fundamental aspect of innovation in materials science. In the ﬁeld of energy conversion, for example, the development of water-processed organic solar cells provides environmentally friendlier materials, which contribute to reduce health risks. Herein, a novel approach is described to produce water-soluble electron-donor single wall carbon nanotube (SWCNT) hybrids based on the noncovalent immobilization of quaternized pyridyloxy zinc phthalocyanines (ZnPc) with a varying number of pyridyl substituents. Moreover, the excellent electron-accepting ability of the latter ZnPcs is reported. The introduction of tert-butylphenyl groups at the pyridines enables for the ﬁrst time a complete characterization. The electron-acceptor nature of the ZnPcs enables switching the role of SWCNTs within the resulting supramolecular hybrids. Finally, a proof-of-concept demonstration of the SWCNT/ZnPc hybrids' capacity for energy conversion is presented, paving their way to possible use as active layer material in solar cells processed entirely from aqueous solutions.
EAM Import::2019-03-13